Українсько-польські взаємини у політиці християнських суспільників Галичини наприкінці XIX – на початку XX ст. - Кліш, А. Б. (Lviv Polytechnic Publishing House, 2016)
Проаналізовано складні взаємини між українцями та поляками у Галичині наприкінці ХІХ – на початку ХХ ст. Показано ставлення християнських суспільників щодо польського питання упродовж 1896–1914 рр. Досліджено методи вирішення міжнаціональних суперечностей партійними діячами, їх ставлення щодо польського питання. З’ясовано, що їхня позиція була толерантною та поміркованою щодо ставлення до поляків. The article analyzes the complex relationships between Ukrainian and Polish in Halychyna in the late XIX – beginning XX century. Showing Christian socials attitude on the Polish question during the 1896–1914. Methods of resolving international conflicts party leaders, their attitude to the Polish question. It was found that their position was moderate and tolerant attitude on the Poles. Interethnic tension in Halychyna had a rising tendency. Christian socials took the stand between radical Ukrainian and Polish political forces. The editors of the newspaper severely criticized Polish administration and the public for obstinacy and at the same time urged Ukrainian national democrats to withdraw from their political arsenal of solely oppositional tactics and to take a more flexible position. Research of the materials published on the pages of newspaper “Ruslan” in question allows to cross the borders of traditional bipolar evaluation of Ukrainian-Polish conflict at the turn of the XIX–XX centuries, to open that surroundings, representatives of which understood the political process as the interaction of opponents and not as a destructive fight of enemies.
Keywords: християнські суспільники; Галичина; польсько-українські взаємини; часопис “Руслан”; християнсько-суспільний рух; Christian socials; Halychyna; Polish-Ukrainian relations; newspaper “Ruslan”; christian social movement; 327(477+438) “18/19”:070(477)